Integrated virtual medical consultations versus traditional clinic care in a public and a private outpatient service. Issue 1 (17th November 2022) - Katz, Ivor; Lane, Cathie; Pirabhahar, Saiyini; Williamson, Paula; Kelly, John; Preece, Rachel; Raghunath, Vishwas; Brown, Mark
Abstract : Objectives: The iConnect Care programme provided integrated 'virtual care' (VC) for patients with chronic kidney disease (CKD) in the South Eastern Sydney Local Health District. VC is an alternative to outpatient care which expedites time to specialists' opinions and is safe. Comparing different outpatient care models is important to understand the role of telehealth and integrated care, especially following the COVID-19 pandemic. This study aimed to compare a VC model with existing CKD outpatient care. Design, participants and setting: A multisite, comparative, retrospective cohort study with parallel groups. 374 patients with mild CKD were recruited (July 2013 and August 2015) from public and private outpatients and followed for 12 months (n=304) or via VC (n=70). Estimated glomerular filtration rate (eGFR) and urine albumin/creatinine ratio (ACR) were compared at baseline, 6 and 12 months. Results: At 12 months, no significant differences existed among groups in eGFR or ACR or haemoglobin, but serum creatinine was lower in the VC cohort. A significant difference existed in time to see a patient from time of referral; 7 days for VC clinic and 35–42 days for outpatient clinic. Patients interviewed felt VC was efficient and they were well managed. Conclusion: VC can be a faster mechanism to access a nephrologist and other specialists. It provided similar outcomes to outpatient care. VC represents an additional assessment and follow-up pathway supported in the community. Time to deliver is similar, but specific resources are needed. It has the potential to evolve into a standard component of chronic disease care.